Legal regulation of the right to work for people with disabilities at the international and national levels - Bryliova, Veronika A. (Journal of the Belarusian State University. International Relations, 2020)
The article is devoted to the analysis of legal regulation of the right to work of people with disabilities. This article analyzes the stages of formation of international standards of the rights of people with disabilities in the sphere of employment, and puts emphasis on the measures that states should implement in domestic law to create equal opportunities, equal treatment, an integrated approach and social inclusiveness. Problematic areas of realization of labour potential are outlined and solutions are proposed as a result of the analysis of the legal regulation of the right to work of people with disabilities in the Republic of Belarus. The proposal to replace the system of workplace reservation for people with disabilities with a quota system, which has proved to be practically effective in a number of countries, has been substantiated. The article emphasizes that the basis for effective employment of people with disabilities is a balance between the guarantees of their rights in the area of employment relations and tax benefits, which encourage employers to provide employment to people with disabilities. The article formulates proposals to improve tax legislation in the Republic of Belarus.
Keywords: people with disabilities; the right to work; implementation of the labour potential; international standards of the right to work; domestic guarantees of the right to work; workplace reservation; job quotas; tax incentives for employers